2021
DOI: 10.1186/s42269-021-00663-2
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical competence and pharmacological perspectives of an endangered boon—Costus speciosus (Koen.) Sm.: a comprehensive review

Abstract: Background Costus speciosus (Koen) Sm. popularly known as crepe ginger or spiral ginger and insulin plant is a perennial rhizomatous herb contain variable number of medicinally important bioactive phytochemicals having intensive pharmacological effects due to antioxidant, antimicrobial, insecticidal, anticancerous, and antidiabetic properties. This plant is widely distributed throughout India and has tremendous ethnobotanical uses. This review article is the coalescence of the distribution, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Phytochemical components and Pharmacological effects of Melissa officinalis: Melissa officinalis is a therapeutic plant rich in organic active components which contains predominantly essential oils (including Citronellal, Menthol, Eugenol, Linalool, Pinocarvone, and Geraniol) and Polyphenols (including Rosmarinic acid, Caffeic acid, Chlorogenic acid, Salicylic acid, Ellagic acid, and Quercetin) that determine several pharmacological effects with possible therapeutic uses (including anti-inflammatory effects, anti-diabetic effects, anti-proliferative effects, anti-angiogenic effects, anti-depressant effects, anti-cancer effects, anti-oxidant effects, anti-microbial effects, anti-epileptic effects, and cardio-protective effects). [25][26][27] of Melissa officinalis on EV71 infection. This study showed that Melissa officinalis aqueous extract prevents loss of viability in EVA71-infected virus cells and Melissa officinalis has a high percentage of antiviral compounds.…”
Section: Enterovirus-71mentioning
confidence: 99%
See 2 more Smart Citations
“…Phytochemical components and Pharmacological effects of Melissa officinalis: Melissa officinalis is a therapeutic plant rich in organic active components which contains predominantly essential oils (including Citronellal, Menthol, Eugenol, Linalool, Pinocarvone, and Geraniol) and Polyphenols (including Rosmarinic acid, Caffeic acid, Chlorogenic acid, Salicylic acid, Ellagic acid, and Quercetin) that determine several pharmacological effects with possible therapeutic uses (including anti-inflammatory effects, anti-diabetic effects, anti-proliferative effects, anti-angiogenic effects, anti-depressant effects, anti-cancer effects, anti-oxidant effects, anti-microbial effects, anti-epileptic effects, and cardio-protective effects). [25][26][27] of Melissa officinalis on EV71 infection. This study showed that Melissa officinalis aqueous extract prevents loss of viability in EVA71-infected virus cells and Melissa officinalis has a high percentage of antiviral compounds.…”
Section: Enterovirus-71mentioning
confidence: 99%
“…The antimicrobial activities of lemon balm are mainly explained through the C15 and C10 terpenes with phenolic hydroxyl groups and aromatic rings, as well as other active terpenes, such as esters, aldehydes, and alcohols. 25 - 27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to (Gupta 2010), C. speciosus is an ornamental tall, rhizomatous, perennial succulent herb that can grow up to 2.7 meters high. The plant's rhizome is covered in sheaths and includes nodes and internodes; as it grows upward, it becomes leafy (Sohrab et al 2021). The plant's thick, upright or occasionally ascending stems bear large, lanceolate, dorsally silky leaves in a helical fashion.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used as a treatment for diabetes [ 12 ]. This plant, popularly known as crepe ginger, spiral ginger, or insulin plant is a perennial rhizomatous herb that contains numerous medicinally important phytochemicals [ 13 ]. The known compounds of C. speciosus have intensive pharmacological effects owing to their antimicrobial, antioxidant, insecticidal, anticancer, and antidiabetic properties.…”
Section: Introductionmentioning
confidence: 99%